Spectroscopic and Computational Observation of Glutamine Tautomerization in the Blue Light Sensing Using Flavin Domain Photoreaction - Hontani, Yusaku; Mehlhorn, Jennifer; Domratcheva, Tatiana; Beck, Sebastian; Kloz, Miroslav; Hegemann, Peter; Mathes, Tilo; Kennis, John T M (Journal of the American Chemical Society, 2023)
Blue light sensing using flavin (BLUF) domains constitute a family of flavin-binding photoreceptors of bacteria and eukaryotic algae. BLUF photoactivation proceeds via a light-driven hydrogen-bond switch among flavin adenine dinucleotide (FAD) and glutamine and tyrosine side chains, whereby FAD undergoes electron and proton transfer with tyrosine and is subsequently re-oxidized by a hydrogen back-shuttle in picoseconds, constituting an important model system to understand proton-coupled electron transfer in biology. The specific structure of the hydrogen-bond patterns and the prevalence of glutamine tautomeric states in dark-adapted (DA) and light-activated (LA) states have remained controversial. Here, we present a combined femtosecond stimulated Raman spectroscopy (FSRS), computational chemistry, and site-selective isotope labeling Fourier-transform infrared spectroscopy (FTIR) study of the Slr1694 BLUF domain. FSRS showed distinct vibrational bands from the FADS1 singlet excited state. We observed small but significant shifts in the excited-state vibrational frequency patterns of the DA and LA states, indicating that these frequencies constitute a sensitive probe for the hydrogen-bond arrangement around FAD. Excited-state model calculations utilizing four different realizations of hydrogen bond patterns and glutamine tautomeric states were consistent with a BLUF reaction model that involved glutamine tautomerization to imidic acid, accompanied by a rotation of its side chain. A combined FTIR and double-isotope labeling study, with 13C labeling of FAD and 15N labeling of glutamine, identified the glutamine imidic acid C═N stretch vibration in the LA state and the Gln C═O in the DA state. Hence, our study provides support for glutamine tautomerization and side-chain rotation in the BLUF photoreaction.
Keywords: fotoreceptory mikroorganismů; Bacterial Proteins; flavinadenindinukleotid; Flavin-Adenine Dinucleotide; glutamin; světlo; Spectroscopy, Fourier Transform Infrared; Tyrosine; organické látky; Protons; Organic Chemicals; Glutamine; spektroskopie infračervená s Fourierovou transformací; bakteriální proteiny; Light; Photoreceptors, Microbial; tyrosin; protony